Commemorating the Glorious Past of Guerillas: An Analysis of Memoirs of Maoist Guerillas - Pokharel, Badri Prasad (Journal of Development Review, 2025)
This article aims to analyze Tara Rai Anmol’s memoir work Chapamar Yuvatiko Dayari (Diary of a Guerrilla Girl) and Nabin Jirel ‘s Bhishan Dinharu (Rigorous Days) with the perspective of trauma theorists like Duncan Bell and Nigel Hunt. Past events related to war and conflicts always bring a horrible consequence to the survivors who, if anything can, remember these historical events as a psychological need and a social duty to reminisce those who died in the battle. Focusing on the historical role in understanding the psychological response to war trauma, this write up elucidates the social factors which play in psychological understanding and building together to develop the concept of the personal narrative – the memoir of an ex-Maoist combatant, Tara Rai and Nabin Jirel who fought in the ten-years long People's War instigated by the then Nepal Communist Party (Maoist) as members of cultural troupe and militant, arrested by the security personnel and spent a long time in jails. This article has tried to illuminate those facts which have made the traumatic past a meaningful one for memorialization and commemoration.